Pembuatan dan Karakterisasi Biodegradable plastic Berbasis Campuran Pati dan Selulosa Dari Limbah Jagung - Ari Susanti; Heri Septya Kusuma; D.K. Zafira; A.B. Ilmi; I.E. Agustina; L Baqih; Arie Prayoga (Eksergi, 2021)
Foodstuffs need proper packaging to prevent spoilage. The use of conventional plastics for packaging has caused environmental problems. It is necessary to develop environmentally friendly packaging as biodegradable plastic. The purpose of this study was to isolate cellulose from corn cobs with three different procedures to determine the best procedure for producing cellulose, as evidenced by the color and results of FTIR analysis. The best cellulose yields are used to make biodegradable plastic films combined with starch and a glycerol plasticizer, sodium montmorillonite nanoclay filler, and clove leaf essential oil. The film that has been made is continued with characterization in the form of analysis of degradation ability, analysis of volatility mass fraction (%), analysis of swelling degree (%), and water solubility (%). The results of this study found that the best cellulose isolation was produced by a procedure 2. The results of the analysis of the degradation ability of the film showed that it was under SNI 7188.7: 2016 with the fastest degradation results within four days with the addition of SMMT. The results of the VMF (%) analysis showed that the presence of EO and SMMT in the composition causes the VMF (%) value to be below. The results of the SD (%) analysis show that the presence of SMMT causes the SD (%) value to increase while the addition of EO causes the SD (%) value to decrease. The results of the WS (%) analysis showed that the presence of SMMT causes the WS (%) to increase, while the addition of EO to the composition variation causes the WS (%) to decrease